Optimalisasi Pemanfaatan Platform Merdeka Mengajar Dan Penguatan P5 Bagi Guru Di Korwil I Bengkulu Utara - Rika Partikasari; Mimpira Haryono; Ranny Fitria Imran; Ela Pebriani; Sisi Oktasari (Universitas Dehasen Bengkulu, 2023)
Year 2024 has become the policy decision for national curriculum based on the evaluation on curriculum during learning recovery. Because of that, Ministry of Education, Culture, Research and Technology (Kemendikbudristek) develops Merdeka Mengajar application (PMM). According to data from BPMP of Bengkulu province during socialization of the implementation of Merdeka Curriculum Implementation on November 2022, there are several schools in North Bengkulu area which has not optimized the use of Mengajar application to support Merdeka Belajar Curriculum program. The purpose of this community service is to change the thinking pattern and give support to teachers at regional coordinator I of North Bengkulu to be more optimize in using Merdeka Mengajar application. The method which used in this community service was by using face to face presentation which conducted at SDN 016 of North Bengkulu for a day. The program was attended by invited 64 participants from 36 schools. After studied the materials together with PKM PGPAUD UNIVED team, the teachers, school operators and headmasters who have registered and have belajar.id account become more motivated and can use the application more optimize. They can also implement the P5 reinforcement in their respective schools.